Vulnerability, trust and microcredit: The case of China's rural poor - Calum G. Turvey; Rong Kong (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper investigates the economic conditions of rural households in China. Historical survey data indicate that over 80 per cent of rural households earn less than 4,500 yuan in net disposable income each year, that for the vast majority of rural households disposable income is insufficient to meet food consumption needs, and that in terms of economic growth rural households are receiving an ever decreasing percentage of China's growing economy with rural household incomes being only 31 per cent of urban household income in 2004. To reduce vulnerability and food insecurity, this paper investigates the role of microcredit in China. It is argued that in China the conventional wisdom is to provide credit using traditional means, but we provide a model that shows how a microcredit market based on trust can co-exist with a commercial collateral-based market.
Keywords: O13; O16; O19; 330; equilibrium; game theory; rural; credit; China; Haushaltseinkommen; Ländliche Armut; Nahrungsmittelversorgung; Mikrofinanz; China